Revision of the systematics of the cardinalfishes (Percomorpha: Apogonidae) based on molecular analyses and comparative reevaluation of morphological characters - Mabuchi, Kohji; Fraser, Thomas H.; Song, Hayeun; Azuma, Yoichiro; Nishida, Mutsumi (Zootaxa, 2014)
Molecular analyses were conducted based on 120 of the estimated 358 species of the family Apogonidae with 33 of 40 genera and subgenera, using three gobioids and one kurtid as collective outgroups. Species of Amioides, Apogon, Apogonichthyoides, Apogonichthys, Archamia, Astrapogon, Brephamia, Cercamia, Cheilodipterus, Fibramia n. gen., Foa, Fowleria, Glossamia, Gymnapogon, Jaydia, Lachneratus, Nectamia, Ostorhinchus, Paroncheilus, Phaeoptyx, Pristiapogon, Pristicon, Pseudamia, Pterapogon, Rhabdamia, Siphamia, Sphaeramia, Taeniamia, Verulux, Vincentia, Yarica, Zapogon and Zoramia were present in the molecular analyses; species of Bentuviaichthys, Holapogon, Lepidamia, Neamia, Paxton, Pseudamiops and Quinca were absent from the analyses. Maximum-likelihood (ML), Bayesian (BA), and Maximum parsimony (MP) analyses based on two mitochondrial (12S rRNA-tRNAVal-16S rRNA, ca. 1500 bp; COI, ca. 1500 bp) and two nuclear DNA (RAG1, ca. 1300 bp; ENC1, ca. 800 bp) fragments reproduced two basal clades within the monophyletic family: one including a single species, Amioides polyacanthus, and the other comprising species of Pseudamia. All the other apogonid species formed a large well-established monophyletic group, in which almost identical 12 major clades were reproduced, with phylogenetic positions of four species (Glossamia aprion, Ostorhinchus margaritophorus, Pterapogon kauderni, and Vincentia novaehollandiae) left unsettled. Apogon sensu lato and recent Ostorhinchus (excepting O. margaritophorus) were divided into six and three major clades, respectively. Each of the recognized clades in the family was then evaluated for morphological characters to identify synapomorphies. Based on the results of the molecular analyses and the reevaluation of morphological characters, four subfamilies were proposed within the family: Apogoninae (including most of the species in the family), Amioidinae new subfamily (including Amioides, and based on morphology, Holapogon), Paxtoninae new subfamily (including Paxton, based only on morphology) and Pseudamiinae (including Pseudamia). Within the largest subfamily Apogoninae, twelve new tribes were proposed based on the 12 molecular clades and associated morphology: Apogonichthyini, Apogonini (mainly including species of Apogon sensu stricto), Archamiini, Cheilodipterini, Gymnapogonini, Ostorhinchini (including striped species of recent Ostorhinchus), Pristiapogonini, Rhabdamiini, Sphaeramiini (mainly including barred species of traditional Ostorhinchus, such as Apogonichthyoides, Jaydia and Nectamia), Siphamiini, Veruluxini, and Zoramiini. Two additional tribes are proposed based only on morphology: Glossamiini and Lepidamiini. For each of the 14 tribes, morphological characters were described. One new genus, Fibramia, type species Apogon thermalis, recently in Ostorhinchus, was described supported by morphology and molecular trees. A key to all genera is provided and all valid and uncertain status species are allocated to tribes and genera.